A social robot to deliver a psychotherapeutic treatment: Qualitative responses by participants in a randomized controlled trial and future design recommendations. Issue 155 (November 2021) - Robinson, Nicole L.; Kavanagh, David J.
Highlights: A social robot can deliver a psychotherapeutic treatment. The robot received positive evaluations on its interactive nature and sociable persona. Detailed recommendations are provided for designing robot interactions for healthcare. Greater personalization in future will allow closer simulations of client-centred counselling. Abstract: This paper reports the design and qualitative evaluation of a social robot programmed to deliver a talk-based treatment program to improve health behaviour change for food intake and weight loss. A qualitative study was conducted to investigate factors that influenced human-robot interaction and its relationship to health treatment outcomes. Semi-structured interviews were undertaken on completion of a randomised controlled trial that used an autonomous robot to deliver a 4-week behavioral intervention to help coach people to decrease the consumption of high calorie foods. Questions focused on individuals' preferences, learnings and outcomes from their participation in the trial. Twenty participants completed the treatment, and 18 conducted an interview. Content analysis found that a social robot to deliver a psychotherapeutic treatment was effective and feasible. Participants did make changes to their health behaviour change with a >50% reduction in high calorie intake and average reduction of 4.4 kilograms in weight loss. The robot received positive evaluations on its interactive nature and sociable persona. Most participants made improvements that were aligned with their chosen health goal after completing the robot-delivered sessions, and reported that the robot sessions helped them to achieve their behaviour change goals, such as consuming fewer high calorie foods. Detailed recommendations are provided for the future design of healthcare interventions by robots, including key considerations for robot behaviour, treatment content, and presentation of the program. Future recommendations are presented for the development of robot personalization to more closely resemble techniques and skills from client-centred counselling.